Pengaruh Kualitas Produk dan Gaya Hidup Terhadap Keputusan Pembelian iPhone melalui Minat Beli Sebagai Variabel Intervening - A Muhammad Ikbal; Siti Hasbiah; Zainal Ruma; Chalid Imran Musa; Muhammad Ilham Wardhana Haeruddin (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the effect of product quality and lifestyle on purchasing decisions for iPhone smartphones through purchase intention as an intervening variable. The sample used was 85 students of the Faculty of Economics and Business, Makassar State University who had been selected based on predetermined criteria. Data collection techniques were carried out by questionnaires, interviews and literature studies. The data analysis technique consists of Outer Model (Measurement Model) which consists of Convergent Validity, Discriminant Validity and Composite Reliability, then Structural Model (Inner Model) and Hypothesis Test. Based on the results showed that the product quality variable has a positive and significant effect on purchasing decisions with a parameter coefficient of 0.192, a t-count value of 2.030, and a p-value of 0.043 <0.05. Lifestyle variables have a positive and significant effect on purchasing decisions with a parameter coefficient of 0.338, t-count value of 3.353 and p-value is 0.001 <0.05. product quality has a positive but insignificant effect on purchase intention with a parameter coefficient of 0.129, t-count value of 1.142 and p-value is 0.254>0.05. Lifestyle has a positive and significant effect on buying interest with a parameter coefficient of 0.558, a t-count value of 6.485 and a p-value of 0.000 <0.05. buying interest has a significant effect on purchasing decisions with a parameter coefficient of 0.558, a t-count value of 6.485 and a p-value of 0.000<0.05.